Aphrodite's Sisters - Stylianou-Lambert, Theopisti; Heraclidou, Antigone; Papantoniou, Giorgos; Morris, Christine (My University, 2022)
Aphrodite became the symbol par excellence of Cypriot archaeology and the island of Cyprus. “Aphrodite’s Sisters” explores the diaspora and multiple social biographies of the most popular Cypriot statue of Aphrodite and its copies: the Aphrodite of Soloi, a marble statue from the 1st century BC, found by a farmer while ploughing his field and donated to the Cyprus Museum in 1902. The original statue - nowadays on display at the Cyprus Museum - is possibly a Roman copy of an earlier Hellenistic statue. Contemporary copies of this statue are scattered in gardens, homes, and shops. Furthermore, the image of the statue travels through promotional material and other products (like those of the Deputy Ministry of Tourism, as well as through the Republic’s passports), thus crossing geographical and political boundaries. This statue is associated with Cyprus like no other and plays a dual role: it promotes the Greek culture of the island and becomes an iconic touristic symbol of Cyprus. “Arte-facts (Aphrodite’s Sisters)” (2017-ongoing), photographs by Theopisti Stylianou-Lambert, set of 6 portraits, 8 x 12 inch each “Aphrodite’s Sisters”, an art project by Theopisti Stylianou-Lambert, explores the diaspora and multiple social biographies of Aphrodite of Soloi and its copies. This iconic statue can be found decorating homes, gardens, offices and shops. The artist photographs the statue with its owners at the location that is found and also interviews the owners about their relationship with the statue. One of the photographs show the original statue found at the Cyprus Museum with Eftychia Zachariou, the Curator of the museum. A selection of portraits is presented here. In order of appearance: Costas, Hambis, Costas M., Eftychia, Andreas and Katerina. “Collecting Aphrodite’s Sisters” (2022), video with crowdsourced material, Theopisti Stylianou-Lambert, Antigone Heraclidou, Giorgos Papantoniou, and Christine E. Morris In 2022 the team announced an open crowdsourcing call in order to collect images of Aphrodite of Soloi and associated stories. About 40 people from Cyprus and abroad responded with their own photographs of Aphrodite found in unexpected places. The photographs and selected text are presented in a video format. Special thanks to CYENS intern Helia Zakeri for her help preparing the video.
Keywords: Aphrodite; photography